Imunização anti-GnRH como um modelo para estudo da suplementação exógena de gonadotrofinas em fêmeas bovinas - Della Méa, Ricardo (2021)
Gonadotropin supplementation is necessary in reproductive biotechnics. In postpartum cows, the use of equine chorionic gonadotropin (eCG) represents the only hormonal alternative to stimulate follicular growth and increase conception rates. Alternatively, the use of FSH was evaluated, however, it was shown to be ineffective due to the short half-life. Studies used the postpartum cow model to study gonatrophin supplementation. Alternatively, implants with GnRH agonists allow to inhibit ovarian activity, limiting the growth of follicles up to 4 mm in diameter. Immunocastration with the commercial anti-GnRH vaccine (Bopriva) can also represent a model, however, it becomes necessary to test its viability. Therefore, the objective was to validate a model to study alternative sources of gonadotropin supplementation. In experiment 1, eight adult cyclic cows received the anti-GnRH vaccine in two doses with an interval of thirty days. Then, the cows were separated into three experimental groups: Group 1: 400UI of eCG, group 2: 50 mg FSH+Pluronic F127 and group 3: 50 mg FSH, with an evaluation of the follicular dynamics. In Experiment 2, six cows were selected, three cyclic (control group) and three in anestrus induced by the use of anti-GnRH vaccine (Bopriva group). On D0, cyclic cows received a vaginal implant containing 1 g of progesterone and 2 mg of estradiol benzoate, while cows in the Bopriva group were not treated. Five days later (D5), treatment with FSH (Folltropin) was started in all cows, administered in eight decreasing applications with an interval of 12 h, totaling 200 mg FSH per cow. In cyclic cows, 500 μg of sodium cloprostenol was administered on D8, when the vaginal implants were removed. In Experiment 3, six cows were immunocastrated with two doses of the anti-GnRH vaccine. On D0, the cows received 830 IU of eCG and 1g of progesterone implant. Forty-eight hours later (D2), another dose of 830 IU of eCG was administered. On D6.5 of the experiment, ovulation was induced by administering 1250 IU of hCG. On D9, ovulation was assessed and blood samples were taken from D6.5 to D14 to measure progesterone concentrations. In experiment 1, all cows responded to treatment with the anti-GnRH vaccine, observing only follicles with a diameter less than 4 mm, showing the effectiveness of the vaccine. However, none of the single-dose treatments induced follicular growth. In Experiment 2, all cows responded to the FSH superovulation protocol, presenting multiple follicles > 8 mm, proving the reversal of the vaccine effect. In experiment 3, after the second application of eCG, four cows responded to treatment with at least one follicle > 10 mm. Cows that presented preovulatory follicles responded to treatment with hCG and ovulated, with progesterone concentrations above 20 ng/mL seven days after treatment, demonstrating the functionality of the corpus luteum. Therefore, it is concluded that immunocastration with anti-GnRH vaccine can be used as a model for the study of alternatives for exogenous gonadotropin supplementation in female bovine animals.